The Sacrosanct Of The Realist Jurisprudential Standpoint - Olusegun, DUROTOLU (Kurdish Studies, 2022)
The study of jurisprudence is rooted in philosophy. It involves an examination of human wisdom as deposited in the minds of many great thinkers on a discreet analysis of societal problems, demands, and what should be the proper roles of the law in engendering a better society. In essence, since opinions in the minds vary, there could not be any convincing and all-embracing definition of jurisprudence. The natural law school posits that law represents the higher laws of an indeterminate sovereign by which man-made law itself must be filtered by the divine law to make it fit to guide against the misconduct of man, both the ruler and the ruled. On the other hand, the positivist legal theorist conceptualises law as the article that emanates from a human sovereign who derives his power from the people, to whom every person is subservient, but himself is subservient to no one. The realist position stresses the importance of the Court's decisions in determining what is, in a real sense, 'the law'. Jurisprudence conceptualised or defined as the wisdom of law is faced with the task of eliciting the wisdoms of the various schools that are faced with the herculean task of defining, and conceptualising what law is, what law ought to be, what are the essentials of legal validity, what is the source of real law in the most practical sense, and how do we get to the ideals of law, among other issues. Legal theorists agree that political powers should not be concentrated in one person or institution, but in collegiate bodies. There was agreement between legal and political theorists that the governmental powers in the state should be separated and manned by separate institutions. Baron de Montesquieu wrote about the theory of the separation of powers. By this theory, the law-making function should be performed by the legislature or the parliament, and the policy formulation and implementation roles should be within the exclusive preserve of the executive arms of government. Then, the law interpretation and adjudication functions should remain exclusively within the judicial domain. With this arrangement, the power to make law could only be performed by the legislative branch and not by any other branch. Meanwhile, the vexing question is how on earth the claim by the Realist could be valid, that nothing pretentious do I mean by the law more than what the Court states, putting it in Oliver Wendell Holmes' words. Again, if the Court itself is a product and creation of the law, on what ground could the judiciary be the progenitor of law? As a product of law, a judicial arm could not be its progenitor. This is contrary to the product of an indeterminate sovereign who is subservient to no one and to whom everybody is subservient. However, the judicial law-making function emanates from the adjudicating tasks of the Court in the course of resolution of disputes, clarification of ambiguities in law, and acting as a check on recalcitrant executives and the parliament, an exercise necessary to check or preventing the legislative arm from passing draconian law at the dictate of virulent executives with the abilities to pass law and implement same with all the violence of an oppressor. Through adjudication, clarification, and checks and balances on other arms of government, the law-making functions of the courts became more profound. Thus, the truism of the Realists takes hold. This paper aims to trace the origin of the realist school, its foundation, its typologies, its characteristics, and the relevance of the realist school in the Nigerian courts.